Effect of Cellulase Enzyme Treatment on Cyst Wall Degradation of Acanthamoeba sp. - Tisha Lazuana; Hendri Astuty; Ika Puspa Sari (Journal of Parasitology Research)
Aim. The goal of this study is to know the potential of cellulase in the degradation of cyst wall Acanthamoeba sp. Methods. Sample of Acanthamoeba sp. obtained from isolate collection of Department of Parasitology FKUI of which two samples come from patient and one sample is from environment. All three samples were cultured using non-nutrient agar (NNA) media and identified by PCR and sequencing. The concentration of cellulase concentration used was 50 U, 100 U, 150 U, 200 U, 250 U, and 300 U with the incubation time used being 2 hours, 4 hours, 6 hours, 8 hours, and 24 hours. Furthermore, treatment results with the most optimum concentration and incubation time were observed by using SEM to see changes in the surface of the walls of the cyst. A cysticidal test was performed to determine the effectiveness cysticidal action of disinfectant solution, cellulase, and the combination of disinfectant solution and cellulase in killing Acanthamoeba sp. cyst assessed by their viability value. Results. The most optimal cellulase concentration in killing Acanthamoeba sp. cysts was 300 U with an incubation time of 24 hours. Percentage of viability of Acanthamoeba sp. which was exposed to a disinfectant solution for 24 hours was 95%, cellulase alone for 24 hours 75%, and the combination of cellulase and disinfectant solution for 24 hours 25%. Conclusions. Cellulase is capable of degrading Acanthamoeba sp. cyst wall. Optimal cellulase concentration in degrading Acanthamoeba sp. cyst wall is 300 U with an optimal incubation time being 24 hours. The addition of cellulase to the disinfectant solution has the potential to increase the effectiveness of the disinfectant solution because cellulase is capable of degrading the cyst wall allowing the disinfectant solution to enter and kill Acanthamoeba sp. cysts.